The Correlation between Students' Intelligence Level and their Achievement in Learning English - Ahmad Junaedi (Acitya: Journal of Teaching and Education, 2021)
The objective of the research was to find out the correlation between the students intelligence and their achievement in learning English at SMPN 27 Makassar. The design of this research was descriptive and employed correlational method. The population of this research was the second year students of SMPN 27 Makassar. The technique of sampling applied cluster random sampling which the total of sample was 20 students. The instruments of this research were IQ test and English test. To find out students achievement in learning English, the researcher tested the students using multiple choice test that consisted of materials from their handbook. To find out the level of students intelligence, the Psychological Department Team of State University of Makassar was given IQ test. To find out the correlation from both variables, the researcher used Pearson r formula. The result of the test shows that most of the students’ intelligence was categorized as dull average and the students’ achievement was 6.35 which is categorized as fair achievement. The result data found that there was no significant correlation between the students’ intelligence level and their achievement in learning English at the second year of SMPN 27 Makassar.